Balancing Voices: Power Relations in Feminist Studies Involving Women with Disabilities in Yogyakarta - Itriyati, Fina; Pradigto Utomo, Hartmantyo (INKLUSI, 2025)
This research addresses a significant gap in ethnographic studies by focusing on women with disabilities in Javanese culture. The objective is to apply an emancipatory, affective feminist ethnographic approach that challenges power dynamics between researchers and participants, addressing issues of social class, disabled and non-disabled identities, and educational differences. Using participant observation, in-depth interviews, and analysis of aural, textual, and visual data, the study explores lived experiences of these women. Key findings indicate that societal pressures, domestic violence, and pity sustain stigmas against disabled communities, whereas empathetic dialogue is essential for genuine narratives. The study advocates for continuous self-reflection to recognize subtle societal biases and calls for research with emancipatory values, amplifying marginalized voices and promoting inclusive policies that address social, psychological, and medical dimensions of women with disabilities. Penelitian ini mengisi kesenjangan signifikan dalam studi etnografi dengan berfokus pada perempuan penyandang disabilitas dalam budaya Jawa. Tujuannya adalah untuk menerapkan pendekatan etnografi feminis yang emansipatoris dan afektif, yang menantang dinamika kekuasaan antara peneliti dan partisipan, serta mengatasi isu-isu kelas sosial, identitas disabilitas dan non-disabilitas, dan perbedaan pendidikan. Dengan menggunakan observasi partisipatif, wawancara mendalam, serta analisis data aural, tekstual, dan visual, studi ini mengeksplorasi pengalaman hidup para perempuan tersebut. Temuan utama menunjukkan bahwa tekanan masyarakat, kekerasan dalam rumah tangga, dan rasa kasihan melanggengkan stigma terhadap komunitas penyandang disabilitas, sedangkan dialog empatik sangat penting untuk menghasilkan narasi yang tulus. Studi ini mendorong refleksi diri yang berkelanjutan untuk mengenali bias masyarakat yang halus dan menyerukan penelitian dengan nilai-nilai emansipatoris, memperkuat suara-suara yang terpinggirkan, serta mempromosikan kebijakan inklusif yang membahas dimensi sosial, psikologis, dan medis dari perempuan penyandang disabilitas.